1999
DOI: 10.1007/s101200050029
|View full text |Cite
|
Sign up to set email alerts
|

Results of surgical therapy in patients with adenocarcinoma of the esophagus and cardia

Abstract: Abstract:Background. Adenocarcinoma of the esophagus and cardia is a challenging disease for the surgeon. Delay in diagnosis, nodal involvement, and incompleteness of resection have an adverse effect on long-term prognosis. Efforts are currently oriented to identify patients who may benefit from extensive resection. Methods. Between November 1992 and May 1998, 218 patients with histologically proven adenocarcinoma of the distal esophagus or cardia were referred to our Department. In 6 patients (10.2%) cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
2
12
1
Order By: Relevance
“…This was most likely due to new developments in surgical techniques and improved preoperative patient selection for laparotomy. The rate of R0 resections in this study was 82.1%, which is consistent with the rate reported in other studies [12, 20]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This was most likely due to new developments in surgical techniques and improved preoperative patient selection for laparotomy. The rate of R0 resections in this study was 82.1%, which is consistent with the rate reported in other studies [12, 20]. …”
Section: Discussionsupporting
confidence: 82%
“…Some investigators have reported a male predominance in CGC [11,12,13]. While we observed a similar tendency, no significant difference was detected in the gender ratio between CGC and DTGC patients.…”
Section: Discussioncontrasting
confidence: 48%
“…The work of Peracchia et al [5] is a major contribution in this context. It has been demonstrated that there is still a need for discussion concerning different treatment and classification (treatment as esophageal cancer or as gastric cancer?)…”
mentioning
confidence: 99%
“…Adenocarcinoma of the esophagogastric junction is one of the most lethal malignancies 1 . The incidence of esophageal adenocarcinoma has been increasing steadily over the past two or three decades, mainly in the United States and Western Europe, surpassing the incidence of squamous cell carcinoma of the esophagus 2–4 .…”
Section: Introductionmentioning
confidence: 99%